Early Positive Approaches to Support (E-PAtS) for Families of Young Children With Intellectual Disability: A Feasibility Randomised Controlled Trial - Coulman, Elinor; Gore, Nick; Moody, Gwenllian; Wright, Melissa; Segrott, Jeremy; Gillespie, David; Petrou, Stavros; Lugg-Widger, Fiona; Kim, Sungwook; Bradshaw, Jill; McNamara, Rachel; Jahoda, Andrew; et al. (Frontiers in Psychiatry, 2021)
Background: Parents of children with intellectual disabilities are likely to experience poorer mental well-being and face challenges accessing support. Early Positive Approaches to Support (E-PAtS) is a group-based programme, co-produced with parents and professionals, based on existing research evidence and a developmental systems approach to support parental mental well-being. The aim of this study was to assess the feasibility of community service provider organisations delivering E-PAtS to parents/family caregivers of young children with intellectual disability, to inform a potential definitive randomised controlled trial of the effectiveness and cost-effectiveness of E-PAtS. Methods: This study was a feasibility cluster randomised controlled trial, with embedded process evaluation. Up to two parents/family caregivers of a child (18 months to <6 years old) with intellectual disability were recruited at research sites and allocated to intervention (E-PAtS and usual practise) or control (usual practise) on a 1:1 basis at cluster (family) level. Data were collected at baseline and 3 and 12 months' post-randomisation. The following feasibility outcomes were assessed: participant recruitment rates and effectiveness of recruitment pathways; retention rates; intervention adherence and fidelity; service provider recruitment rates and willingness to participate in a future trial; barriers and facilitating factors for recruitment, engagement, and intervention delivery; and feasibility of collecting outcome measures. Results: Seventy-four families were randomised to intervention or control (n = 37). Retention rates were 72% at 12 months post-randomisation, and completion of the proposed primary outcome measure (WEMWBS) was 51%. Recruitment of service provider organisations and facilitators was feasible and intervention implementation acceptable. Adherence to the intervention was 76% and the intervention was well-received by participants; exploratory analyses suggest that adherence and attendance may be associated with improved well-being. Health economic outcome measures were collected successfully and evidence indicates that linkage with routine data would be feasible in a future trial. Conclusions: The E-PAtS Feasibility RCT has demonstrated that the research design and methods of intervention implementation are generally feasible. Consideration of the limitations of this feasibility trial and any barriers to conducting a future definitive trial, do however, need to be considered by researchers. Clinical Trial Registration:https://www.isrctn.com, identifier: ISRCTN70419473.